Back to basics: Gaps in baseline data call for revisiting an environmental education program in the SAVA region, Madagascar. - Marina B Blanco; Alexie N Rudman; Lydia K Greene; Fusiane Razafindrainibe; Lanto Andrianandrasana; Charles Welch (PLoS ONE, 2020)
Environmental education programs are critically important for raising awareness about global and local environmental concerns, by providing the knowledge, tools, and means for young and old generations to cope with current challenges. Of the greatest importance is the implementation of environmental education programs in biodiversity hotspots where environmental crises are high and resources to fund mitigation programs are low. Madagascar is one such priority hotspot, featuring intensive wildlife-human conflicts due to shrinking natural environments. The Duke Lemur Center-SAVA Conservation Initiative has been conducting environmental education activities in the SAVA region, northeastern Madagascar, since 2011. These activities have been aimed at increasing awareness of local and global environmental issues and at stimulating the involvement of local school students. Our initiatives have predominantly supported teacher trainings to provide teachers with environmental education content, examples, and recommendations on how to integrate activities into their regular curricula, commonly referred to as a "cascade approach". Due to logistical hurdles, including high teacher turnover rates, however, these interventions have not been monitored to assess their efficacy. Thus, to better inform current and future interventions, we designed and implemented classroom-based surveys to gather baseline data on the basic knowledge of SAVA students and their perceptions of the environment. We identify informational gaps in surveyed schools, including those located in large towns vs. villages, and those with trained vs. untrained teachers. Based on these results, we make recommendations for future environmental education efforts in the region, including activities that could address real-life environmental problems and decision-making solutions.